Pengaruh Penambahan Serat Kawat Bendrat Berbentuk “U” Terhadap Sifat Mekanis Beton - Irvan, Ridho Kurnia Putra; Ismeddiyanto, Ismeddiyanto; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Concrete is the main ingredient in the construction world, because the concrete is easy to work and economical in terms of cost, but the concrete is considered to have low tensile strength compared with the compressive strength, so the need for effort in improving the mechanical properties of the concrete mixing fiber in concrete mixture is wrong One attempt to improve the mechanical properties of concrete one of them by using fiber wire bedrators formed into "U" with a total length of 9 cm. The specimen consists of a cylindrical specimen with a diameter of 150 mm and a height of 300 mm and a beam with a length of 600 mm, a width of 150 mm, and a height of 150 mm. The fiber length used is 9 cm with 0.0%, 0.25%, 0.50%, 0.75% 1.0% of the fiber mass variation from the aggregate fraction. Non-fiber concrete is made for comparison. The method of mixing fiber into the concrete mixture is randomly after the concrete is evenly mixed. The results showed compressive strength, splitng tensile strength and maximum bending strength at 0.5% fiber variation. According to the results of the study, the addition of wire fiber to concrete mixture can improve the mechanical properties of concrete and in the optimal fiber variation can be at 0.5%.Keywords : fiber concrete, fiber wire bedrators, compressive strenght, splitting tensile strength, flexural strength